Regulatory Function of Herbal Drug-Partitioned Moxibustion for Sub-Health Status - 刘延英 黄国琪（翻译） (Journal of acupuncture and tuina science, 2007)
摘要目的观察隔药灸治疗亚健康状态的疗效及对体液免疫、 细胞免疫、 血液流变学的影响。方法采用中医健康评估的方法, 选出研究对象, 根据不同的发生原因、 症状、 临床表现, 辨证取穴、 隔药施灸, 同时监测治疗前后各项理化指标及临床症状的变化。结果隔药灸后临床症状有明显改善, NK细胞活性、 血小板聚集性均有明显变化, 与灸前比较差异均有统计学意义(P<0.05)。 同时治疗后体液免疫中补体C3、 补体C4 含量下降, 免疫球蛋白IgG含量上升, 与治疗前比较均有统计学意义(P<0.05)。结论隔药灸能调节亚健康人体的脏腑气血功能, 使机体阴阳平衡, 精足气充神旺, 从而改善亚健康状态, 并提示对亚健康人体的体液免疫、 细胞免疫及血液流变有调节作用。ObjectiveTo observe the efficacy of herbal drug-partitioned moxibustion for sub-health status and its influence on humoral immunity, cellular immunity and blood rheology.MethodsBy health evaluation in traditional Chinese medicine, the subjects were selected and applied with herbal drug-partitioned moxibustion on the acupoints selected upon pattern identification, in accordance with different causative reason, symptoms, clinical manifestations, to observe the changes in various physiochemical indexes and clinical symptoms before and after the treatments.ResultsAfter herbal drug-partitioned moxibustion, the clinical symptoms were obviously improved, and obvious change took place in the activity of NK cells and in platelet aggregation, with statistic significance (P<0.05) in comparison of those before moxibustion. Simultaneously, the contents of C3 and C4 decreased in humoral immunity after the treatment, and IgC content increased, with statistic significance (P<0.05) in comparison of those before the treatment.ConclusionHerbal drug-partitioned moxibustion can regulate the functions of qi and blood in those with sub-health, by balancing yin and yang in the body and invigorating the spirit and reinforcing qi, so as to relieve sub-health status, indicating its regulatory function on humoral immunity, cellular immunity and blood rheology of the human body.